Stroke Risk Following Takotsubo Cardiomyopathy - Morris, Nicholas A. (Neurohospitalist, 2020)
BACKGROUND AND PURPOSE: Takotsubo cardiomyopathy, also known as stress cardiomyopathy, is an increasingly recognized cause of left ventricular dysfunction. Previously considered a benign disease, Takotsubo cardiomyopathy may be a risk factor of ischemic stroke based on recent small, single-center case series. The strength and temporal profile of this association remains uncertain. METHODS: We performed a cohort-crossover study using administrative claims data on all emergency department visits and acute care hospitalizations from 2005 to 2015 in California, New York, and Florida. We identified patients with Takotsubo cardiomyopathy, excluding those with a prior or concomitant stroke diagnosis. We compared the risk of ischemic stroke in the first year after Takotsubo cardiomyopathy to the risk of ischemic stroke in the second year after Takotsubo cardiomyopathy. Takotsubo cardiomyopathy and ischemic stroke were ascertained using previously validated ICD-9-CM codes. Absolute risks and odds ratios (OR) were calculated using McNemar test for matched data. RESULTS: Among 5283 patients with Takotsubo cardiomyopathy (mean age, 67 years; 92% female), we identified 49 ischemic strokes during the first year after Takotsubo cardiomyopathy versus 19 ischemic strokes during the second year after. The risk of stroke was significantly higher in the year after Takotsubo cardiomyopathy (absolute increase, 0.6%; 95% CI: 0.2-0.9; OR: 2.6; 95% CI: 1.5-4.6) as compared to the control period. CONCLUSION: We found a heightened risk of ischemic stroke in the year after a diagnosis of Takotsubo cardiomyopathy, although the absolute risk increase was small.